Rational and Irrational Investor Sentiments and Stock Market Returns: Evidence from the Tehran Stock Exchange - Mohammad Nadiri; Hamid Reza Panahian (تحقیقات مالی)
ObjectiveNumerous studies have focused on developing theoretical frameworks to examine the relationship between stock returns and investor sentiment dynamics. In contrast to earlier studies, which treated investor sentiments as entirely irrational, Verma et al. (2008) added to the literature a new framework that divides sentiment into fundamentals-driven (rational sentiment) and irrational components (irrational sentiment). Furthermore, they explored the possibility of a dynamic relationship between individual and institutional investor sentiments, which had been ignored in previous research. This study aims to investigate the impact of rational and irrational investor sentiments, both individual and institutional, on the overall index returns of the Tehran Stock Exchange. MethodsTo test the research hypotheses, we first used Baker and Wurgler's (2007) method to extract the sentiment index of individual and institutional investors using Principal Component Analysis (PCA), and then we investigated the hypotheses using two methods and two steps. In the first step, we used an autoregressive distributed lag (ARDL) technique to regress macroeconomic fundamental variables on individual and institutional investor sentiments to decompose the sentiment variables into rational and irrational components. In the next step, the effect of rational and irrational investor sentiment on stock market returns was evaluated using the vector autoregressive (VAR) approach on monthly data from 2011 to 2020. ResultsThe Granger causality test and impulse response functions from VAR model estimation show that the rational component of individual and institutional investors positively and significantly affects market returns. For both individual and institutional investors, it was discovered that the impact of rational sentiments on stock market returns was greater than the impact of irrational sentiments. Furthermore, the findings show that past stock market performance has a significant unidirectional impact on irrational sentiments but has no effect on rational sentiments for individual and institutional investors. The research indicates that rational sentiments have pricing power in the Tehran Stock Exchange. Under such conditions, the rational expectations theory of stock returns is a valid argument for the Tehran Stock Exchange. Overall, the results indicate that sentiment-induced fundamental investing has a much more significant effect on individual and institutional investors than sentiment-induced noise trading in the long run. ConclusionThe findings have important implications for investors and policymakers. Individuals, particularly inexperienced investors, are encouraged to trade in these markets with adequate information, expertise, and market analysis. They should avoid herding and emotional trading and maintain a long-term perspective on the stock market. Furthermore, the stock exchange organization and related financial institutions should assist in reducing emotional behaviors and increasing the efficiency of the stock market by enhancing the financial literacy of inexperienced retail investors and strengthening the investment culture. Today, the sentiment index is used as a financial market predictor, so it is essential for the institutions in charge of regulating the financial markets to be involved in the compilation, reporting, and analysis of this index. In the event of extreme price fluctuations or market deviations (even in the short term), these institutions should issue the necessary and timely warnings and support the effectiveness of the market by approving and implementing control mechanisms such as short selling.